Retrospective Analysis of Patients with Genitourinary Fistula - Serdar Başaranoğlu; Ayşegül Deregözü; Şafak Hatırnaz; Coşkun Şahin; Sedat Kadanalı (Medical Network, 2017)
Objective: To present the outcomes of patients treated at a tertiary center for a diagnosis of genitourinary fistula secondary to gynecological and obstetric etiologies. Study Design: In this retrospective study, analysis was made of 18 patients with a diagnosis of genitourinary fistula in a tertiary center between January 2006 and June 2016. Patient data were taken from the archives and patient histories. A record was made of examinations, diagnostic methods such as cystoscopy and fistulography and appropriate medical treatments, demographic data, intraoperative and post-operative complications, duration of hospital stay, surgical operations and types, diameter and location of fistulas. Results: Of the 18 cases, 14 were secondary to obstetric trauma. In 10 of these 14 cases, fistula had developed after difficult vaginal delivery and in four cases, after caesarean section. Four of the 18 cases were secondary to gynecological surgeries, namely hysterectomy and cystocele repairs. Vesicovaginal fistulas were repaired transvaginally while vesicouterine fistulas and bilateral ureterovaginal fistulas were repaired transabdominally. The mean hospital stay was 3.8±1.5 days (2-7 days). Patients were followed up closely in the first 3 months and recurrence developed in only one case. Conclusion: Fistulas secondary to gynecological procedures are uncommon while fistulas secondary to inadequate perineal care, insufficient labor monitoring and difficulties in vaginal delivery techniques are more prevalent in Turkey. Thorough evaluation, using all diagnostic tools for complete diagnosis, understanding the pathophysiology and choosing the best surgical procedure are mandatory to obtain good outcomes after the surgical